Developmental defects and p53 hyperacetylation in Sir2 homolog (SIRT1)-deficient mice - Cheng, Hwei-Ling (National Academy of Sciences, 2003)
SIRT1 is a mammalian homolog of the Saccharomyces cerevisiae chromatin silencing factor Sir2. Dominant-negative and overexpression studies have implicated a role for SIRT1 in deacetylating the p53 tumor suppressor protein to dampen apoptotic and cellular senescence pathways. To elucidate SIRT1 function in normal cells, we used gene-targeted mutation to generate mice that express either a mutant SIRT1 protein that lacks part of the catalytic domain or has no detectable SIRT1 protein at all. Both types of SIRT1 mutant mice and cells had essentially the same phenotypes. SIRT1 mutant mice were small, and exhibited notable developmental defects of the retina and heart, and only infrequently survived postnatally. Moreover, SIRT1-deficient cells exhibited p53 hyperacetylation after DNA damage and increased ionizing radiation-induced thymocyte apoptosis. In SIRT1-deficient embryonic fibroblasts, however, p53 hyperacetylation after DNA damage was not accompanied by increased p21 protein induction or DNA damage sensitivity. Together, our observations provide direct evidence that endogenous SIRT1 protein regulates p53 acetylation and p53-dependent apoptosis, and show that the function of this enzyme is required for specific developmental processes.